AB0618 Nailfold Capillaroscopy Changes during Pregnancy in Connective Tissue Diseases. (15th July 2016) - Meroni, M.; Ramoni, V.L.; Brucato, A.L.; Limonta, M.; Pizzorni, C.; Cutolo, M.
Abstract : Background: Nailfold videocapillaroscopy (NVC) changes early appear in connective tissue diseases (CTDs): besides the "scleroderma pattern" of systemic sclerosis (SSc), abnormalities have been reported in mixed connective tissue disease (MCTD) and undifferentiated connective tissue disease (UCTD) [1]. Pregnancy can modify the course of of CTDs [2]. NVC changes during pregnancy have been described in healthy women [3], but no data are available regarding CTD subjects during pregnancy. Objectives: Our study aimed to investigate if there is an impact of pregnancy on NVC changes, and of which kind, among CTDs patients. Methods: After Local Ethic Committee approval and informed consent signature, we prospectively enrolled 29 consecutive pregnant women, with an established diagnosis of CTD (either SSc, MCTD or UCTD) and RP from at least 12 months. Pregnant women underwent a NVC examination at conception (defined as T0) and, after that, to a second one (T1), between the beginning and the end of the third trimester of gestation. The pregnant subjects are referred as "cases". In parallel, 29 non-pregnant women with the same diagnosis, comparable underlying disease duration and similar age of cases were matched in retrospect ("controls"). NVC was performed in all 29 couples of patients by the same operator, at baseline (T0) and follow-up (T1) (Videocap, DS MediGroup, Milan, Italy). The following capillaroscopic parameters were considered: number of capillaries per area; presence of ectasic capillary and megacapillaries; haemorrhages (hemosiderin deposits); loss of capillaries, disorganization of the microvascular array and capillary ramifications (combined, their constitute the "microangiopathy evolution score"-MES); tortuosity; edema. A semiquantitative rating scale was adopted to score each capillary abnormality (0=no changes; 1=less than 33% of capillary alterations/reduction; 2=33–66% of capillary alterations/reduction; 3=more than 66% of capillary alterations/ reduction) [4]. Statistical analysis was conducted by non-parametric tests. Results: Among 29 cases (and 29 matched controls), we collected 14 UCTD, 10 MCTD and 5 SSc. Regarding capillaroscopic abnormalities, the two groups were homogeneous at T0, whereas statistically significant differences (excepted for ectasias and tortuosity scores) were observed at T1. Capillary number increased only among cases (pregnant women; p<0.001). Hemosiderin deposition and architectural subversion scores were reduced in cases and increased in controls (both, p<0.05). Megacapillary, MES, ramifications and edema scores progressed only in controls (all, p<0.05), while capillary number reduction score (consistently with absolute capillary number per mm 2 ) was abated in pregnant cases. Conclusions: Our work investigated for the first time pregnancy influence on NVC aspects in CTDs; considering the number of statistical differences in capillaroscopic abnormalities between the two groups at the follow-up, it suggests that pregnancy could play a protective role against microvascular damage progression in CTDs subjects. References: Nagy Z, Czirják L. J Eur Acad Dermatol Venereol. 2004;18:62–8. Tincani A, et al. Hematol Rep 2006;2:56–60. Linder HR, at al. Eur J Obstet Gynecol Reprod Biol. 1995;58:141–5. Sulli A et al. Ann Rheum Dis 2008;67:885–7. Disclosure of Interest: None declared